2021
DOI: 10.3390/ani11123469
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Genetic Background and Selection Signatures of Huaxi Cattle Using High-Density SNP Array

Abstract: Huaxi cattle, a specialized beef cattle breed in China, has the characteristics of fast growth, high slaughter rate, and net meat rate, good reproductive performance, strong stress resistance, and wide adaptability. In this study, we evaluated the genetic diversity, population structure, and genetic relationships of Huaxi cattle and its ancestor populations at the genome-wide level, as well as detecting the selection signatures of Huaxi cattle. Principal component analysis (PCA) and phylogenetic analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Genetic diversity is an important index to measure the degree of population variation and the status of germplasm resources [19]. Jianli pigs had Ho of 0.21 and He of 0.22, which were comparable with those of most Chinese indigenous breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity is an important index to measure the degree of population variation and the status of germplasm resources [19]. Jianli pigs had Ho of 0.21 and He of 0.22, which were comparable with those of most Chinese indigenous breeds.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs are a common type of genetic variation present throughout the genome. They are extensively utilized for various research purposes, including the evaluation of germplasm resources, analysis of genetic diversity, and the study of phylogenetic evolution [ 15 17 ]. Current SNP typing methods commonly include whole genome sequencing (WGS), genotyping by sequencing (GBS), and commercial SNP chips.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of selection signals is vital to uncover the genes related to economic traits and explore the adaptation mechanism of domestication. In recent years, several statistical methods have been used to detect recent selection footprints in composite populations, including comprehensive haplotype score (iHS), complex likelihood ratio (CLR), crosspopulation extended haplotype homozygosity (XP-EHH), and interpopulation relatively comprehensive haplotype homozygosity (Rsb) [15,16]. For example, based on the Illumina BovineLD v2 BeadChip data, van der Nest.…”
Section: Introductionmentioning
confidence: 99%
“…Ma. et al identified potentially selected genes at the genome-wide level in Huaxi cattle, which related to ion binding and muscle growth and differentiation [15].…”
Section: Introductionmentioning
confidence: 99%